Implementing Dynamic Assessments in Psychotherapy. (August 2016) - Hopwood, Christopher J.; Thomas, Katherine M.; Luo, Xiaochen; Bernard, Nicola; Lin, Yanli; Levendosky, Alytia A.
In this article, we organize multimethod, multitimescale data around the interpersonal situation, a conceptual framework that can be used to integrate personality, psychopathology, and psychotherapy constructs in order to guide the assessment of clinical dynamics. We first describe the key variables of the interpersonal situation model and articulate methods for assessing those variables as they manifest (a) across different levels of personality, (b) across situations, and (c) within situations. We next use a case to demonstrate how to assess aspects of the interpersonal situation in a manner that enhances case conceptualization and facilitates the evaluation of clinical hypotheses. We also use this case to highlight challenges and decisions involved in implementing dynamic assessment in psychotherapy. We conclude by outlining areas in need of further exploration toward a more sophisticated approach to clinical practice that involves the routine assessment of dynamic processes.